The ethics of Catholicism and the consecration of the intellectual - Bélanger, André J., 1935- (McGill-Queen's University Press, 1997)
Using France as the most representative case of a Catholic context, Andre J. Belanger argues that as French society became more secularized intellectuals replaced the clergy as arbitrators of justice and enlightenment. Catholic morality was consolidated by the scholastic tradition and confirmed by the Counter-Reformation, providing the foundation that allowed the establishment of a lay elite. Belanger describes the progressive takeover of positions of influence by the new elite in Catholic society and examines arguments used by thinkers from the seventeenth to the twentieth century to legitimize their positions. In contrast, the Anglo-Saxon Protestant tradition, due to its emphasis on the priesthood of all believers, led to recognition of the individual's conscience as the sole judge of her or his deeds and failed to provide intellectuals with the basis for any claim to serve as moral leaders in political affairs.